Odpowiedzi

2009-10-03T13:01:59+02:00
2/3 : [ 1/3 + 3(2-2/3*2/3)] +6 = 3/2 [ 1/3 + 3 ( 2 - 4/9 )] + 6 = 3/2 * [ 1/3 + 3 ( 1 i 5/9 )] + 6 = 3/2 * ( 1/3 + 3 * 14 /9 ) + 6 = 3/2 * (1/3 + 14/3 ) + 6 = 3/2 * 15/3 + 6 = 15/2 + 6 = 7 i 1/2 + 6 = 13 i 1/2

3 i 14/9 musisz skrocic dlatego wyszlo 14/3 i 3/2 oraz 15/3 wyszlo 15/2

16 * (1/4) do kwadartu - 2
----------------------------------- + 1/4 =
2,1 - 6,4 * ( 1/4 ) do trzeciej


16 * 1/16 - 2
----------------------------- + 1/4 =
21/10 - 64/10 * 1/64

-1
-------------------- + 1/4 =
21/10 - 1/10

-1
-------- + 1/ 4 =
20/10

-1: 2 + 1/4 = -1/2 + 1/4 = - 2/4 + 1/4 = - 1/ 4

2009-10-03T13:20:16+02:00
B) ²/₃ : [¹/₃+3(2-⅔ * ⅔)]+ 6 = ²/₃ : [¹/₃+3(2-⁴/₉)]+6=
= ²/₃ : [ ¹/₃+6-1²/₉]+6= ²/₃ : [ ¹/₃+6-1³/₉]+6=
= ²/₃ : [¹/₃+4⁶/₉]+6= ²/₃ : [³/₉+ 4 ⁶/₉]+6= ²/₃*⁵/₁+6=
= ¹⁰/₃+6= 6 ¹⁰/₃ = 9¹/₃


e)16*(¼) ² - 2 16*¹/₁₆-2
-------------------=--------------------------- = 16 skróci się z ¹/₁₆
2,1-6,6*(¼) ³ 2 ¹/₁₀-6⁶/₁₀*¹/⁶⁴

-1 -1 -1
= -----------=------------ =----------= ³⁴/₁₀ skracamy z¹/₆₄ przez 2
-3⁴/₁₀*¹/₆₄ -³⁴/₁₀*¹/₆₄ ¹⁷/₃₂₀

= -1: ¹⁷/₃₂₀ = -1*³²⁰/₁₇= dzielenie odwrotnością mnożenia


= -³²⁰/₁₇=18¹⁴/₁₇ wyciągamy całości